Conductive material dispersion liquid, preparation method and application thereof, positive electrode and lithium secondary battery
By using hydrogenated nitrile rubber (HNBR) as a dispersant, combined with carbon nanotubes and N-methylpyrrolidone (NMP) as a dispersion medium, a conductive material dispersion liquid was prepared, which solved the problem of dispersion difficulty of carbon nanotubes in electrode materials, and achieved the improvement of conductivity uniformity and the performance of lithium secondary batteries.
Patent Information
- Application Number
- CN202411893771.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the dispersion of carbon nanotubes in electrode materials is difficult, resulting in uneven conductivity and affecting the performance of lithium secondary batteries.
Hydrogenated nitrile rubber (HNBR) is used as a dispersant, combined with carbon nanotubes and N-methylpyrrolidone (NMP) as dispersion medium, to prepare a conductive material dispersion liquid, and achieve uniform dispersion of carbon nanotubes through π-π interaction and Coulomb repulsion force.
The dispersion and solid content of conductive carbon materials are improved, the conductivity of carbon nanotubes is fully utilized, the specific capacity and cycle stability of lithium secondary batteries are enhanced, and the risk of cracking of the electrode sheet is reduced.
Smart Images

Figure CN119725536A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of conductive materials and lithium secondary batteries, and in particular to a conductive material dispersion liquid, a preparation method and application thereof, a positive electrode and a lithium secondary battery. Background Art
[0002] In the design and development of high-performance batteries, especially lithium secondary batteries, the selection and optimization of electrode materials are key links in improving battery performance. Electrode materials must have both excellent ion migration capabilities and efficient electronic conductivity to ensure stable operation of the battery under high load and high power conditions. However, electrodes composed of a single active material often have large internal impedance, which leads to obstructed ion flow and accumulation of negative charges at the positive electrode, thereby interfering with the orderly migration of positive ions and ultimately weakening the overall performance of the battery.
[0003] To solve this problem, the industry generally adopts the strategy of adding conductive agents to electrode materials, aiming to build a continuous conductive network, strengthen the conductivity of the electrode, and enable the active material to fully exert its energy storage potential. Among them, nano-scale particles, due to their unique size effect, can not only accelerate the embedding and extraction process of ions, but also effectively maintain the stability of the electrode structure, making them ideal conductive additives. Conductive carbon materials such as acetylene black, Ketjen black, carbon fiber, carbon nanotubes and graphene are therefore very popular.
[0004] In particular, carbon nanotubes (CNTs) have become the preferred material for improving electrode conductivity due to their excellent fibrous conductivity and mechanical strength. However, due to their high aspect ratio, strong van der Waals attraction, and insolubility in most solvents, carbon nanotubes are very likely to self-aggregate and form aggregates, which seriously affects their uniform distribution and performance in electrode materials. Therefore, in practical applications, how to effectively disperse carbon nanotubes has become a technical challenge that needs to be solved urgently.
[0005] At present, the dispersion technology of carbon nanotubes is mainly divided into two categories: physical method and chemical method. Although physical methods such as ultrasonic vibration and mechanical shearing can achieve a certain degree of dispersion, they often have high energy consumption, low efficiency, and may damage the structural integrity of carbon nanotubes. Chemical methods, including covalent bond modification and non-covalent bond modification, change the surface properties of carbon nanotubes by introducing functional groups or adsorbed molecules to achieve dispersion. However, these methods often involve complex chemical reactions and may introduce impurities, affecting battery performance.
[0006] Polyvinyl pyrrolidone (PVP) is a commonly used dispersant in industrial electrode slurries. Its pyrrolidone group can form π-π interactions with the surface of carbon nanotubes, providing a certain dispersion effect. However, PVP is prone to oxidative decomposition under high voltage, which not only damages battery performance but also may cause safety hazards. At the same time, PVP has limited dispersibility. For carbon nanotube products with smaller particle sizes and higher dispersion difficulties, its dispersion effect is often unsatisfactory.
[0007] In summary, the development of a new, efficient and stable conductive material dispersion and its preparation method is of great significance for improving the conductivity of battery electrodes, optimizing battery structure and extending battery life. The present invention aims to solve the carbon nanotube dispersion problem existing in the prior art, and provides a conductive material dispersion suitable for high-performance lithium secondary batteries and its preparation method, as well as a positive electrode and a lithium secondary battery prepared using the dispersion. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a conductive material dispersion liquid and a preparation method and application thereof, a positive electrode and a lithium secondary battery.
[0009] In a first aspect, the present invention provides a conductive material dispersion, the conductive material dispersion comprising a dispersant, a conductive agent and a dispersion medium;
[0010] The dispersant is hydrogenated nitrile rubber, and the physical and chemical property parameters of the hydrogenated nitrile rubber include: weight average molecular weight of 10000-300000 g / mol, molecular weight distribution index of 1.5-6.0, Mooney viscosity of 10-60 ML (1+4) 100°C, unsaturation of 0.1-10%, and combined acrylonitrile mass fraction of 15-50%;
[0011] The conductive agent includes carbon nanotubes;
[0012] The dispersion medium includes N-methylpyrrolidone.
[0013] Furthermore, the physical and chemical properties of the carbon nanotubes include: an average diameter of 1-30 nm, a BET specific surface area of 100-300 m 2 / g.
[0014] Furthermore, based on 100 parts by weight of the conductive material dispersion, the amount of the carbon nanotubes added is 0.1 parts by weight to 20 parts by weight; based on 100 parts by weight of the carbon nanotubes, the amount of the dispersant added is 0.1 parts by weight to 20 parts by weight.
[0015] Furthermore, the rotational viscosity of the conductive material dispersion is 0-2000 mPa·S.
[0016] In a second aspect, the present invention provides a method for preparing the conductive material dispersion according to any one of the first aspects, the preparation method comprising the following steps:
[0017] obtaining a dispersant;
[0018] The dispersant, the conductive agent and the dispersion medium are stirred and mixed to obtain the conductive material dispersion.
[0019] In a third aspect, the present invention provides a use of the conductive material dispersion described in any one of the first aspect and / or the conductive material dispersion obtained by the preparation method described in any one of the second aspect in preparing positive electrode slurry, positive electrode and lithium secondary battery.
[0020] In a fourth aspect, the present invention provides a positive electrode, which comprises, by weight, an aluminum foil current collector and a positive electrode active material layer formed by a positive electrode slurry composition coated on the aluminum foil current collector; the positive electrode slurry composition comprises the following raw materials: the conductive material dispersion described in any one of the first aspects and / or the conductive material dispersion obtained by the preparation method described in any one of the second aspects, a positive electrode active material and a binder;
[0021] Based on 100 parts by weight of the positive electrode active material, the added amount of the binder and the conductive agent is 2 parts by weight to 4 parts by weight.
[0022] Further, the positive electrode slurry composition has a solid content concentration of 40-60wt%, a rotational viscosity of 1000-6000mPa·S, a slurry fineness of 10-30μm, and a viscosity increase rate of 1%-5% after standing for 6h;
[0023] The coating rate of the positive electrode slurry composition on the aluminum foil current collector is 4-8 m / min, the coating thickness is 60-150 μm, and the vacuum drying temperature of the electrode sheet after coating is 100-120° C. for 10-15 h;
[0024] The physical and chemical properties of the positive electrode include: peel strength of 15-75N / m, compaction density of 2-4g / cm 3 .
[0025] In a fifth aspect, the present invention provides a lithium secondary battery, comprising: the positive electrode and negative electrode as described in any one of the fourth aspects, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
[0026] Furthermore, the physical and chemical properties of the lithium secondary battery include: a cycle capacity of 140-170 mAh g -1 The capacity retention rate after 500 cycles is 70-97%.
[0027] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:
[0028] The embodiment of the present invention provides a conductive material dispersion liquid and a preparation method and application thereof, a positive electrode and a lithium secondary battery. The conductive material dispersion liquid provided by the present invention can improve the dispersibility and solid content of the conductive carbon material, give full play to the conductivity of the carbon nanotubes, and can operate at a high voltage, thereby indirectly improving the specific capacity of the battery; at the same time, the prepared pole piece has good uniformity, inhibits cracking, and improves the problem of cracking of the pole piece, thereby improving the performance characteristics of the battery. Specifically:
[0029] 1) Using hydrogenated nitrile rubber (HNBR) instead of traditional PVP dispersant can solve the above problems well. Nitrile polymer materials have better charge transfer ability, electrochemical compatibility and mechanical strength. On the one hand, nitrile polymer materials can provide enough cyanide groups to interact with carbon tubes to provide a strong anchoring effect. On the other hand, cyanide groups (-C≡N-) can provide carbon tubes with a negative colloidal structure due to their relatively high electronegativity. In this way, the carbon tubes are dispersed by Coulomb repulsion. At the same time, the hydrocarbon polymer chain acts as a way to increase steric hindrance to inhibit the movement, adsorption and agglomeration of carbon tubes, thereby improving dispersibility and giving full play to the excellent conductivity of carbon nanotubes.
[0030] 2) In addition, the cyanide group of nitrile polymer materials can also coordinate lithium ions, thereby increasing the ion transfer rate; the cyanide group (-C≡N-) in nitrile polymer materials will have a strong coordination bond interaction with the transition metal ions, which act as electron donors and electron acceptors respectively, which increases the energy barrier for the irreversible migration of transition metal ions to lithium vacancies and reduces the dissolution of transition metal ions in the electrolyte, thereby indirectly increasing the specific capacity of the battery.
[0031] In summary, the present invention obtains a conductive material dispersion and a lithium secondary battery manufactured using the same by controlling the mass fraction of acrylonitrile combined with HNBR as a CNT dispersant, weight average molecular weight, Mooney viscosity, degree of unsaturation, etc. HNBR provides enough cyano groups to interact with carbon tubes to provide a strong anchoring effect. On the other hand, cyano groups (-C≡N-) can provide a negatively charged colloidal structure to carbon tubes due to their relatively high electronegativity, so that the carbon tubes are dispersed by Coulomb repulsion. At the same time, its hydrocarbon polymer chain is used as a way to increase steric hindrance to inhibit the movement, adsorption and agglomeration of carbon tubes, thereby improving dispersibility and giving full play to the excellent conductivity of carbon nanotubes. At the same time, it can operate at high voltage, indirectly improving the specific capacity of the battery; at the same time, the obtained pole piece has good uniformity, inhibits cracking, improves the problem of cracking of the pole piece, thereby improving the performance characteristics of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0034] Figure 1 This is the blank sample test result.
[0035] Figure 2 The peak at about 4.8 V belongs to the decomposition peak test result of hydrogenated butyronitrile.
[0036] Figure 3 The viscosity change test results of HNBR dispersed CNT slurry. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0039] The first object of the present invention is to provide a conductive material dispersion and a method for preparing the conductive material dispersion, wherein the conductive material dispersion can improve the dispersibility and solid content of the conductive carbon material, give full play to the conductivity of the carbon nanotubes, and can operate at a high voltage, thereby indirectly improving the specific capacity of the battery; at the same time, the prepared pole piece has good uniformity, inhibits cracking, and improves the problem of cracking of the pole piece, thereby improving the performance characteristics of the battery.
[0040] A second object of the present invention is to provide a composition for forming an electrode of a lithium secondary battery, the composition comprising the conductive material dispersion.
[0041] In addition, a third object of the present invention is to provide an electrode for a lithium secondary battery manufactured using the conductive material dispersion, and a lithium secondary battery including the electrode, wherein the lithium ion secondary battery has the advantages of high energy density and excellent cycle performance under high voltage operation.
[0042] In a first aspect, the present invention provides a conductive material dispersion and a method for preparing the conductive material dispersion, which comprises: a conductive material of carbon nanotubes; a dispersant; and a dispersion medium. The carbon nanotubes include single-walled CNTs, few-walled CNTs, and multi-walled CNTs; the dispersant includes HNBR; and the dispersion medium includes NMP.
[0043] In some embodiments, the dispersant (hydrogenated nitrile rubber, HNBR) of the present invention is self-made, and its preparation method comprises the following steps:
[0044] 30g of nitrile rubber [acrylonitrile mass content 35%, Mooney viscosity ML (1+4) 100°C 35] and 270g of anhydrous chlorobenzene were added to a 500ml stainless steel reactor, and a catalyst was added after complete dissolution, with the amount being 0.03% of the nitrile rubber, and nitrogen was replaced for half an hour, and the temperature was raised to 100°C for olefin metathesis reaction. After the reaction for 1 hour, the temperature was raised to 145°C, and then hydrogen was introduced until the pressure reached 7Mpa, so that the nitrile rubber was subjected to metathesis degradation and hydrogenation reduction reaction, and the reaction was carried out for 4 hours to obtain a liquid hydrogenated nitrile rubber solution. After flocculation, washing and drying, a liquid hydrogenated nitrile rubber raw rubber was obtained.
[0045] The characteristic parameters of the obtained liquid hydrogenated nitrile rubber raw rubber are as follows: molecular weight (Mw) is 45176, molecular weight distribution index is 2.28, acrylonitrile content is 35%, and hydrogenation degree is 99%.
[0046] According to the present invention, HNBR provides enough cyano groups to interact with carbon nanotubes to provide a strong anchoring effect. On the other hand, the cyano groups (-C≡N-) can provide a negatively charged colloidal structure to the carbon nanotubes due to their relatively high electronegativity, so that the carbon nanotubes are dispersed by Coulomb repulsion. At the same time, the hydrocarbon polymer chain is used as a way to increase the steric hindrance to inhibit the movement, adsorption and agglomeration of the carbon nanotubes, thereby improving the dispersibility and giving full play to the excellent conductivity of the carbon nanotubes.
[0047] In some embodiments, the physical and chemical property parameters of the hydrogenated nitrile rubber include: a weight average molecular weight of 10,000-300,000 g / mol, a molecular weight distribution index of 1.5-6.0, a Mooney viscosity of 10-80 ML (1+4) 100°C, an unsaturation of 0.1-10%, and a combined acrylonitrile mass fraction of 15-50%; the physical and chemical property parameters of the carbon nanotubes include: an average diameter of 1-30 nm, a BET specific surface area of 100-300 m2 / g.
[0048] According to still another embodiment of the present invention, there is provided a composition for forming an electrode of a lithium secondary battery, the composition comprising a conductive material dispersion.
[0049] In some embodiments, the CNT solution has a mixing amount of 0.1 to 20 parts by weight based on 100 parts by weight of the solution, and the HNBR dispersant has a mixing amount of 0.1 to 20 parts by weight based on 100 parts by weight of the CNT.
[0050] Preferably, in the CNT solution, the mixing amount of the CNT is 1 to 10 parts by weight based on 100 parts by weight of the solution, and the mixing amount of the HNBR dispersant is 1 to 5 parts by weight based on 100 parts by weight of the CNT.
[0051] According to another embodiment of the present invention, a lithium secondary battery electrode and a lithium secondary battery manufactured using the conductive material dispersion are provided, comprising the following steps: using a coating machine to coat the positive electrode slurry on one side of an aluminum foil current collector to form a positive electrode active material layer; placing the coated electrode sheet in a vacuum oven to dry to obtain a positive electrode sheet.
[0052] According to the present invention, a conventional preparation method can be used to add HNBR dispersed CNT slurry into the positive electrode active material layer to obtain a positive electrode sheet with uniform coating, suppressed cracking and high voltage resistance.
[0053] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0054] The preparation method of HNBR used in the following examples and comparative examples of the present invention is as follows:
[0055] 30g of nitrile rubber [acrylonitrile mass content 35%, Mooney viscosity ML (1+4) 100°C 35] and 270g of anhydrous chlorobenzene were added to a 500ml stainless steel reactor, and a catalyst was added after complete dissolution, with the amount being 0.03% of the nitrile rubber, and nitrogen was replaced for half an hour, and the temperature was raised to 100°C for olefin metathesis reaction. After the reaction for 1 hour, the temperature was raised to 145°C, and then hydrogen was introduced until the pressure reached 7Mpa, so that the nitrile rubber was subjected to metathesis degradation and hydrogenation reduction reaction, and the reaction was carried out for 4 hours to obtain a liquid hydrogenated nitrile rubber solution. After flocculation, washing and drying, a liquid hydrogenated nitrile rubber raw rubber was obtained.
[0056] The characteristic parameters of the obtained liquid hydrogenated nitrile rubber raw rubber are as follows: molecular weight (Mw) is 45176, molecular weight distribution index is 2.28, acrylonitrile content is 35%, and hydrogenation degree is 99%.
[0057] Embodiment 1:
[0058] (1) Preparation of HNBR pre-dispersion
[0059] 8 g of HNBR was dissolved in 92 g of NMP, and the temperature was raised to 40° C. and stirred to dissolve.
[0060] The weight average molecular weight of hydrogenated butyronitrile is 40000g / mol, the molecular weight distribution is 2.5, and the Mooney viscosity is 20ML(1+4)100℃
[0061] (2) Preparation of HNBR-dispersed CNT slurry
[0062] The total weight of 5 wt% carbon nanotubes, 1.0 wt% HNBR and 94 wt% NMP were mixed and the CNT slurry was ground to a particle size of 30 μm using a ball mill.
[0063] (3) Preparation of positive electrode slurry
[0064] 33.6 mg of PVDF, 875 mg of 4% CNT conductive agent solution with HNBR as dispersant, and 35 mg of Super-P conductive agent powder were added to the mixing cup and placed in the THINKY stirring and degassing machine, with a speed of 2000 rpm and high-speed mixing for 2 minutes; 33.6 mg of HNBR binder solution was added, with a speed of 2000 rpm and high-speed mixing for 2 minutes; then 2.2 g of high-nickel ternary layered oxide positive electrode active material was added, with a speed of 1500 rpm and high-speed mixing for 2.5 minutes. Among them, the mass fraction of combined acrylonitrile of HNBR dispersant is 33%, the weight average molecular weight is 40000 g / mol, the Mooney viscosity is 20ML(1+4)100℃, and the unsaturation is 0.5%.
[0065] (4) Preparation of positive electrode sheet
[0066] The mixed positive electrode slurry was coated on a 20μm thick aluminum foil current collector using an automatic coating machine to a coating thickness of 120μm, and then placed in a 120℃ vacuum oven for drying for 12h. The dried positive electrode sheet was rolled with a roller press at a pressure of 120t, and the rolled sheet was cut into 4.1×6.3cm pieces using a sheet slitting machine. 2 size.
[0067] (5) Preparation of secondary batteries
[0068] Using porous polypropylene as separator, LiPF6 (Composition: 1.2M LiPF 6 , EC:EMC=3:7, +2%VC) as electrolyte, commercial graphite (graphite:Super-P:CMC:SBR=94:3:1.5:1.5) as negative electrode. Use the electrode slitting machine to cut the negative electrode into 4.3×6.5cm 2 The size of the battery is 1000×100, the separator is disposed between the positive electrode and the negative electrode, and the battery is assembled using a stacking method. The above electrolyte is injected into the assembled battery to prepare the secondary battery of Example 1 for subsequent testing of electrochemical performance.
[0069] Embodiment 2:
[0070] An HNBR pre-dispersion, CNT slurry, positive electrode slurry, positive electrode sheet and secondary battery were prepared in the same manner as in Example 1, except that the weight average molecular weight of hydrogenated butyronitrile was 40,000 g / mol, the molecular weight distribution was 2, and the Mooney viscosity was 20 ML (1+4) 100°C.
[0071] Embodiment 3:
[0072] An HNBR pre-dispersion, CNT slurry, positive electrode slurry, positive electrode sheet and secondary battery were prepared in the same manner as in Example 1, except that the weight average molecular weight of hydrogenated butyronitrile was 60,000 g / mol, the molecular weight distribution was 2.5, and the Mooney viscosity was 20 ML (1+4) 100°C.
[0073] Comparative Example 1:
[0074] A CNT slurry, a positive electrode slurry, a positive electrode sheet and a secondary battery were prepared in the same manner as in Example 1, except that the dispersant in the CNT solution was PVP.
[0075] Comparative Example 2:
[0076] CNT slurry, positive electrode slurry, positive electrode sheet and secondary battery were prepared in the same manner as in Example 1, except that the dispersant in the CNT solution was hydrogenated butyronitrile with a weight average molecular weight of 200,000 g / mol, a molecular weight distribution of 2, and a Mooney viscosity of 40 ML (1+4) 100°C.
[0077] Comparative Example 3:
[0078] CNT slurry, positive electrode slurry, positive electrode sheet and secondary battery were prepared in the same manner as in Example 1, except that the dispersant in the CNT solution was hydrogenated butyronitrile with a weight average molecular weight of 200,000 g / mol, a molecular weight distribution of 2.5, and a Mooney viscosity of 40 ML (1+4) 100°C.
[0079] Test Case
[0080] 1. Dispersant voltage resistance performance test
[0081] Conductive carbon black was added to the HNBR solution to prepare a 10% NMP solution (HNBR: Super-P = 1: 1), coated on aluminum foil, dried in an oven at 80°C for 12 hours, and cut into discs. The negative electrode shell was placed flat on an insulating table, the gold lithium sheet was placed in the center of the negative electrode shell, and the metal lithium sheet was flattened with a sheet press, and then the diaphragm was placed flat on the upper layer of the lithium sheet, and an appropriate amount of electrolyte was added to the surface of the diaphragm with a pipette. The test electrode, gasket, spring sheet and positive electrode shell were placed on the upper layer of the diaphragm in sequence with insulating tweezers, and the active material side of the test electrode should be close to the diaphragm. A button cell was made and a linear voltammetry scan was performed at a scan rate of 0.1mV from 2.1V to 5.2V.
[0082] 2. Viscosity stability monitoring
[0083] The HNBR pre-dispersed liquid, NMP, and carbon nanotubes were mixed at 25° C. for 60 minutes using a homomixer, and the total weight of the composition contained 5 wt % of carbon nanotubes, 1.0 wt % of a dispersant, and 94 wt % of a dispersion medium.
[0084] The results are shown in Table 1.
[0085] Table 1
[0086]
[0087] 3. Electrode resistivity test
[0088] NCM622: conductive agent: PVDF = 98.0-98.6%: 0.4-1.0%: 1.0%, mix the slurry to prepare the positive electrode slurry, and coat it on the PET film to test the resistivity.
[0089] The results are shown in Table 2. The resistivity of the carbon tube slurry with HNBR as dispersant is lower than that of PVP, which proves that HNBR can make the carbon tube disperse more evenly and give full play to the original advantages of carbon tube.
[0090] In addition, the resistivity of the carbon tube slurry electrode using the HNBR dispersant synthesized by this patent is lower than that of other commercial HNBR, which proves that the HNBR synthesized by this patent can make the carbon tube dispersion more uniform and the viscosity reduction effect better.
[0091] Table 2
[0092]
[0093] 4. Battery cycle stability test
[0094] After the slurry of the embodiment is made into a soft-pack battery, a cycle test is carried out to record the capacity retention rate after a certain number of cycles at 0.5C and between 3 and 4.2V.
[0095] The results are shown in Table 3.
[0096] Table 3
[0097]
[0098]
[0099] in addition, Figure 1 This is the blank sample test result. Figure 2 The peak at about 4.8V belongs to the decomposition peak test result of hydrogenated butyronitrile. Figure 3 The viscosity change test results of HNBR dispersed CNT slurry.
[0100] In summary, the embodiments of the present invention provide a conductive material dispersion, a preparation method and application thereof, a positive electrode and a lithium secondary battery. The conductive material dispersion provided by the present invention can improve the dispersibility and solid content of the conductive carbon material, give full play to the conductivity of the carbon nanotubes, and can operate at a high voltage, thereby indirectly improving the specific capacity of the battery; at the same time, the prepared pole piece has good uniformity, suppresses cracking, and improves the problem of cracks in the pole piece, thereby improving the performance characteristics of the battery.
[0101] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0102] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A conductive material dispersion, characterized in that: The conductive material dispersion comprises a dispersant, a conductive agent and a dispersion medium; The dispersant is hydrogenated nitrile rubber, and the physical and chemical property parameters of the hydrogenated nitrile rubber include: weight average molecular weight of 10000-300000 g / mol, molecular weight distribution index of 1.5-6.0, Mooney viscosity of 10-80 ML (1+4) 100°C, unsaturation of 0.1-10%, and combined acrylonitrile mass fraction of 15-50%; The conductive agent includes carbon nanotubes; The dispersion medium includes N-methylpyrrolidone.
2. The conductive material dispersion according to claim 1, characterized in that: The physical and chemical properties of the carbon nanotubes include: an average diameter of 1-30 nm, a BET specific surface area of 100-300 m 2 / g.
3. The conductive material dispersion according to claim 1, characterized in that: Based on 100 parts by weight of the conductive material dispersion, the amount of the carbon nanotubes added is 0.1 parts by weight to 20 parts by weight; based on 100 parts by weight of the carbon nanotubes, the amount of the dispersant added is 0.1 parts by weight to 20 parts by weight.
4. The conductive material dispersion according to claim 1, characterized in that: The rotational viscosity of the conductive material dispersion is 0-2000 mPa·S.
5. A method for preparing a conductive material dispersion according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: obtaining a dispersant; The dispersant, the conductive agent and the dispersion medium are stirred and mixed to obtain the conductive material dispersion.
6. Use of the conductive material dispersion according to any one of claims 1 to 4 and / or the conductive material dispersion obtained by the preparation method according to claim 5 in preparing positive electrode slurry, positive electrode and lithium secondary battery.
7. A positive electrode, characterized in that In parts by weight, the positive electrode comprises an aluminum foil current collector and a positive electrode active material layer formed by a positive electrode slurry composition coated on the aluminum foil current collector; the positive electrode slurry composition comprises the following raw materials: the conductive material dispersion according to any one of claims 1 to 4 and / or the conductive material dispersion obtained by the preparation method according to claim 5, a positive electrode active material and a binder; Based on 100 parts by weight of the positive electrode active material, the added amount of the binder and the conductive agent is 2 parts by weight to 4 parts by weight.
8. The positive electrode according to claim 7, characterized in that The positive electrode slurry composition has a solid content concentration of 40-60wt%, a rotational viscosity of 1000-6000mPa·S, a slurry fineness of 10-30μm, and a viscosity increase rate of 1%-5% after standing for 6h; The coating rate of the positive electrode slurry composition on the aluminum foil current collector is 4-8 m / min, the coating thickness is 60-150 μm, and the vacuum drying temperature of the electrode sheet after coating is 100-120° C. for 10-15 h; The physical and chemical properties of the positive electrode include: peel strength of 15-75N / m, compaction density of 2-4g / cm 3 .
9. A lithium secondary battery, characterized in that: The lithium secondary battery comprises: the positive electrode according to any one of claims 7 to 9, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
10. The lithium secondary battery according to claim 9, characterized in that: The physical and chemical properties of the lithium secondary battery include: a cycle capacity of 140-170 mAh g in a voltage window of 2.7-4.5 V. -1 The capacity retention rate after 500 cycles is 70-97%.
Citation Information
Patent Citations
Positive electrode active material pre-dispersion composition, positive electrode for secondary battery, and lithium secondary battery comprising same
CN109845005A
Conductive material dispersion liquid, composition for secondary battery electrode using same, electrode film, and secondary battery
CN117157775A
Positive electrode conductive paste, positive electrode paste, positive plate, lithium ion battery and preparation method
CN117334911A
Conductive material dispersion liquid, positive electrode slurry, method for producing positive electrode for non-aqueous electrolyte secondary battery, positive electrode for non-
CN119054029A
Composite positive electrode slurry, positive electrode and preparation method thereof
CN119133455A